The effects of levamisole, receiving diets, and pre and post transit potassium on gain and health of stressed calves - F.K. Brazle; Frank Blecha; J.B. McLaren; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1985)
We purchased 264 calves (125 bulls and 139 steers) in Tennessee and transported them to Kansas to evaluate the effects of levamisole injections and potassium supplementation, before and after transit, and feedlot receiving rations on performance and health of stressed calves. The calves were held for 48 to 96 hours in the order-buyer barn, fed either a 1.1% or 1.5% potassium (K) ration, transported for 24 hours, and fed either a 40% concentrate or hay-plus protein-supplement receiving diet fortified with either 1.1 or 1.7% K for 28 days. They were met in Kansas with 16 hr of cold driving rain, followed by severe cold temperatures, so stress was extreme. Subsequently, the calves grazed native pasture for 60 days. Levamisole reduced (P.05) in all groups. Fewer of the calves fed the 1.5% K pretransit diet died during the first 3 days in the feedlot than of those fed the control diet, but the posttransit K (1.7% K) diet resulted in a trend toward higher mortality during the receiving period.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Levamisole; Diets; Potassium; Gain; Health